2019
DOI: 10.3389/frobt.2019.00073
|View full text |Cite
|
Sign up to set email alerts
|

INTRApersonal Synchrony as Constituent of INTERpersonal Synchrony and Its Relevance for Autism Spectrum Disorder

Abstract: INTERpersonal synchrony leads to increased empathy, rapport and understanding, enabling successful human-human interactions and reciprocal bonding. Research shows that individuals with Autism Spectrum Disorder (ASD) exhibit difficulties to INTERpersonally synchronize but underlying causes are yet unknown. In order to successfully synchronize with others, INTRApersonal synchronization of communicative signals appears to be a necessary prerequisite. We understand INTRApersonal synchrony as an implicit factor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 87 publications
(108 reference statements)
2
32
0
Order By: Relevance
“…Time perception is encoded in the motor system and is influenced by action (Merchant & Yarrow, 2016;Wiener, Zhou, Bader, & Joiner, 2019;Yon, Edey, Ivry, & Press, 2017). Indeed, a number of interesting recent studies have explored timing differences in autism within the context of interpersonal communication (Bloch, Vogeley, Georgescu, & Falter-Wagner, 2019;Georgescu et al, 2020;Zampella, Csumitta, Simon, & Bennetto, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Time perception is encoded in the motor system and is influenced by action (Merchant & Yarrow, 2016;Wiener, Zhou, Bader, & Joiner, 2019;Yon, Edey, Ivry, & Press, 2017). Indeed, a number of interesting recent studies have explored timing differences in autism within the context of interpersonal communication (Bloch, Vogeley, Georgescu, & Falter-Wagner, 2019;Georgescu et al, 2020;Zampella, Csumitta, Simon, & Bennetto, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Time on the macrolayer is not always directly experienced, but remains in the background while we live our lives ( Fuchs, 2005 , 2013 ; Vogel et al, 2020 ). This implicit experience in time is observable in a variety of temporal phenomena, such as habit ( Howell, 2015 ; Fuchs, 2018 ), corporeality/embodiment ( Fuchs, 2005 ; Wehrle, 2020 ), historical circumstances ( Kupke, 2009 ), and intersubjectivity/synchronicity ( Fuchs, 2005 , 2013 ; Bloch et al, 2019 ) [also see von Gebsattel, 1954a , p. 137f for a similar distinction between experienced time (“erlebter Zeit”) and lived time (“gelebter Zeit”)]. However, this implicit temporality on the macrolayer of time is still potentially consciously accessible for us through either reflection or may impose on us under certain circumstances, as we will demonstrate in more detail in the section Enduring Situatedness .…”
Section: The Macrolayer and The Microlayer Of Timementioning
confidence: 99%
“…Another review study suggested inter-and intra-personal asynchrony in autistic individuals, suggesting an altered experience of time and atypical integration of audial, visual and motor sensory inputs (Bloch et al, 2019). Temporal deviations in various sensory inputs are most likely to influence behaviour related to the ability to establish and maintain synchronous, reciprocal engagement with others, and therefore, may contribute to social-communication difficulties in autism.…”
Section: Temporal Synchrony In Autism: a Systematic Reviewmentioning
confidence: 99%
“…Temporal deviations in various sensory inputs are most likely to influence behaviour related to the ability to establish and maintain synchronous, reciprocal engagement with others, and therefore, may contribute to social-communication difficulties in autism. Indeed, it has been proposed that diagnostic practices would benefit from assessing a wider presentation of symptoms associated with autism, and measures of interpersonal alignment could serve as implicit measures aiding diagnosis (Bloch et al, 2019).…”
Section: Temporal Synchrony In Autism: a Systematic Reviewmentioning
confidence: 99%